Democratic coordination and eco-social crises. Issue 4 (4th July 2022) - Forman, Fonna; Owen, David; Tully, James
ABSTRACT: Today we confront planetary crises at a time when our structures of governance are characterised by 'dysfunctionality', 'hollowing out', 'gridlock' and democratic governance faces 'antagonistic self-destruction', 'authoritarian supersession', or 'death of democracy'. How should we address this predicament? This paper proposes an approach grounded in acknowledging different modes of democratic citizenship and in recognizing that addressing eco-social crises requires coordination among them. We distinguish five modes of democratic practice against the backdrop of a distinction between two general pictures of citizenship and illustrate how different modes of democratic citizenship (e.g. participatory citizens and Gaia citizens) may 'join hands' to address shared challenges. This approach, we propose, brings to light a slow but sure means of democratic change and transformation.